DRAKOR RASA KOPIKO (Analisis Komunikasi Pemasaran Kopiko Pada Drama Korea Vincenzo - Ari Susanti (Universitas Muhammadiyah Jember, 2021)
Kopiko is a coffee-flavoured candy brand from Indonesia produced by PT Mayora Indah Tbk. The appearance of the Kopiko candy advertisement in the Korean drama Vincenzo had made Indonesian audiences excited. Although Kopiko's products are known to several countries and produce advertisements regularly, Indonesians are indifferent and don't even know about it. This phenomenon is interesting to study from the aspect of marketing communication where Kopiko tries to use alternative marketing strategies by becoming a sponsor in a Korean Drama. This study uses a qualitative descriptive method by analyzing the phenomenon of kopiko advertisements that appear in the Korean drama Vincenzo widely and clearly. Korean dramas have been accepted by the Indonesian people, especially their fans. In this study, it was found that the number of Korean drama fans in Indonesia, Kopiko's reputation, the impact of staying at home during the Covid 19 pandemic until the trade cooperation between Indonesia and South Korea was signed further paved the way for Kopiko to become a sponsor in the Korean drama Vincenzo 2021.